2021
DOI: 10.1097/md.0000000000025627
|View full text |Cite
|
Sign up to set email alerts
|

Tumor attenuation and quantitative analysis of perfusion parameters derived from tri-phasic CT scans in hepatocellular carcinoma

Abstract: The aim of the current study was to explore the value of tumor attenuation and quantitative analysis of perfusion parameters obtained from traditional tri-phasic CT scans in grading hepatocellular carcinoma (HCC). Totally 39 patients (42 lesion samples) with pathologically confirmed HCC who underwent tri-phasic CT scans were enrolled. HCC lesions were divided into non-poorly differentiated HCC (NP-HCC; n = 31) and poorly differentiated HCC (pHCC; n = 11). All lesions were divided into 5 groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…pCT assesses dynamic variations in tissue iodine concentration over time, allowing to obtain tissue-specific data, including blood flow (BF), blood volume (BV), time to peak concentration (TTP), vascular permeability surface area product (PS), and permeability ( K trans), which can be utilised as biomarkers for tumour vascularization and perfusion. Several authours showed that pCT is a considerable tool for lesion characteritation, treatment response assessment, and prognosis [ 96 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…pCT assesses dynamic variations in tissue iodine concentration over time, allowing to obtain tissue-specific data, including blood flow (BF), blood volume (BV), time to peak concentration (TTP), vascular permeability surface area product (PS), and permeability ( K trans), which can be utilised as biomarkers for tumour vascularization and perfusion. Several authours showed that pCT is a considerable tool for lesion characteritation, treatment response assessment, and prognosis [ 96 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…pCT is highly promising as a functional vascular imaging technique. However, because of the increased radiation dose, CT perfusion of liver is largely unfulfilled clinically [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…pCT measures dynamic changes in tissue iodine concentration over time, allowing for calculation of tissue-specific parameters, including blood flow (BF), blood volume (BV), time to peak concentration (TTP), vascular permeability surface area product (PS), and permeability (Ktrans), which can be used as surrogates for tumor vascularization, vascular immaturity, and perfusion pressure. Several researchers reported that pCT is argued to be a significant method for differentiating benign from malignant lesions, evaluating treatment response, and defining angiogenesis [64][65][66].…”
Section: Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis and staging of HCC can be achieved by CT ( Figure 3 ) or MRI ( Figure 4 ) in the absence of invasive methods, when precise and stringent criteria are applied [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Although MRI proves to be more sensitive in the characterization of liver lesions, particularly with hepatospecific contrast agents, there is no unambiguous indication from the pool of experts [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Li-radsmentioning
confidence: 99%